PEMANFAATAN PANAS PADA DINDING KOMPOR GASIFIKASI BIOMASSA UNTUK PEMBANGKIT LISTRIK DC MENGGUNAKAN THERMOELECTRIC GENERATOR - Armansyah, Dian Hadi; Elfiano, Eddy; Yulianto, Dody (Journal of Renewable Energy and Mechanics, 2020)
The stove is one technology that plays an important role in the utilization of energy at the household scale. The biomass stove studied was a blower system gasification stove. In the blower system, oxygen entering the combustion chamber flows continuously according to the needs of combustion. In this biomass gasification stove study, researchers will also use the biomass stove wall or thermal energy into kinetic energy for grinding blowers and charging systems. This study aims to obtain fuel by utilizing biomass or organic waste as biomass stove fuel and get the energy driving the blower and charging system by utilizing a thermoelectric generator system. biomass stoves used in this study use the principle method of Top-Lif Up Draft (T-LUD) Gasifier, a type of gasifier that matches the characteristics of biomass that has high volatile matter, where the stove is designed intended for biomass fuel from agricultural waste products and industry, boiling 1 kg of water is done using wood chips by varying the area of ​​the air flow door, which is 50%, 75%, and 100%. Can be analyzed Comparison of the performance of the biomass cooker stove and the power generated by the thermoelectric generator, at each door width of the air flow results are different, this is due to the mass of fuel consumption and fire temperature. After calculating the highest thermal efficiency results obtained in the area of ​​50% air flow ventilation and obtained power generated 1.83 watts with 100% ventilation flow door area using wood chips.